Rapid determination and quantitation of compositional carbohydrates to identify honey by capillary zone electrophoresis. Issue 4 (2nd October 2017) - Lu, Yalong; Hu, Yuanyuan; Wang, Tong; Yang, Xingbin; Zhao, Yan
ABSTRACT: A simple, sensitive, and specific capillary electrophoretic method based on 1-phenyl-3-methyl-5-pyrazolon (PMP) derivatization has been developed for simultaneous separation and determination of 11 aldoses (maltose, xylose, arabinose, ribose, glucose, rhamnose, fucose, galactose, mannose, glucuronic acid, and galacturonic acid). The separation of PMP-labeled maltose and monosaccharides was carried out under the selected optimum conditions with pH 11.0, 200 mM borate buffer containing 4% methanol at voltage 20 kV, and capillary temperature 25°C, and the 11 PMP aldoses could be perfectly separated from each other within 41 min. Our experiment results demonstrated that the molar ratios of carbohydrates in 10 kinds of honey were greatly different, and the carbohydrates' constitutions varied greatly between commodity honey and natural honey. This proposed zone electrophoresis method provides an accurate and economic alternative for monosaccharide and maltose analysis to identify honeys, and can also be applied to routine detection of reducing carbohydrates in real-life samples.